2005
DOI: 10.1093/gerona/60.8.984
|View full text |Cite
|
Sign up to set email alerts
|

Increased Kinin Levels and Decreased Responsiveness to Kinins During Aging

Abstract: Kinins are vasoactive peptides released from precursors called kininogens, and serum levels of both T- and K-kininogens increase dramatically as rats age. Kinin release is tightly regulated, and here we show that serum kinin levels also increase with age, from 63 +/- 16 nmol/L in young Fisher 344 rats to 398 +/- 102 nmol/L in old animals. Both K- and T-kininogens contribute sequentially to this increase, with the increase in middle-aged animals being driven primarily by K-kininogen, whereas the further augment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Moreover, aging is associated with a decreased availability of cardiac BK B2 receptors 16 and in some occasions with a blunted endothelium-dependent vasodilator response to BK. 17,18 In addition, combined B2 receptor …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, aging is associated with a decreased availability of cardiac BK B2 receptors 16 and in some occasions with a blunted endothelium-dependent vasodilator response to BK. 17,18 In addition, combined B2 receptor …”
mentioning
confidence: 99%
“…Moreover, aging is associated with a decreased availability of cardiac BK B2 receptors 16 and in some occasions with a blunted endothelium-dependent vasodilator response to BK. 17,18 In addition, combined B2 receptor knockout and diabetes mellitus in mice lead to an accelerated aging phenotype that is coupled to an increase of oxidative stress and an increase in ACE enzyme levels. 19 Therefore, the protective effect of BK might also relate to the prevention of cellular senescence, in particular, of the endothelium.…”
mentioning
confidence: 99%
“…C1-INH-HAE results from the uncontrolled release of bradykinin from high molecular weight kininogen (HMWK) due to the de ciency of functional C1-INH. Previous studies have observed the level of kininogen increased with age in rat serum [17][18][19][20] . However, aging leads to weaker responsiveness to kinins [8] which is believed to be realized by the decreased density of the bradykinin receptors, lessening the vasoactive effects of bradykinin on the heart and vasculature [21][22][23] .…”
Section: Discussionmentioning
confidence: 84%
“…Aging does not only affect the KKK system through the ACE/ACE2 balance, but also directly altering the pharmacology of BR1 and BR2. It has been observed that although the serum levels of kinins increase with age, the responsiveness of target cells is limited or altered [ 106 ]. In this respect, bradykinin-induced vasorelaxation is actually affected by the BR1/BR2 ratio in the vasculature [ 107 ].…”
Section: Pathophysiological Contributions Of Covid-19 Risk Factorsmentioning
confidence: 99%